First-Principles Study of the Electrochemical Sodiation of Rutile-Type Vanadium Dioxide. (2020) - Koch, Daniel; Manzhos, Sergei
Abstract: We investigate, from first principles, the electrochemical sodiation mechanism of rutile-type vanadium dioxide as a possible electrode material for sodium-ion batteries. The computed voltages versus sodium metal are low in comparison to current state-of-the-art sodium-ion battery cathodes, which we can relate to the large space demand of sodium ions in the compact rutile structure and the resulting severe lattice deformations compared to other working metals. Due to the same reason large anisotropic unit cell volume changes are predicted during cycling. We furthermore find a change of the preferred reaction mechanism during discharge, with a switching between insertion- and conversion-type reaction at higher degrees of sodiation. The predicted capacities on the other hand are appreciable, making a further consideration of this material as high-potential anode in combination with sodium working metal interesting.